The Slavic and East European Journal (JSTOR)
The Slavic and East European Journal (SEEJ) publishes research studies in all areas of Slavic languages, literatures, and cultures. A book review section is also included in each issue.
Keywords: Area Studies, Humanities, Language & Literature, Slavic Studies